Design and Creating a Specific Neutron Irradiation Instrument to Decrease the User’s Radiation Exposure Time - Muslim, Ahmed Ghanim; Al-Mashhadani, Asia H. (Iraqi Journal of Science, 2023)
A specialized irradiation instrument "created instrument" was  designed and created from various kinds and sizes of available plastic household-waste materials. In addition, a neutron beam collimator with a lid was designed  and implemented. The collimator is with dimensions of 25 cm in height and 10 cm in inner diameter, while the lid dimensions are 11.5 cm height and outer diameter of 9.9 cm  to perfectly match the inner diameter of the collimator with the possibility of movement (opening and closing), and also the shielding of the radioactive 241Am/Be neutron source with a recent activity of 37.5 mCi.To investigate the efficiency of the "created instrument", ten hydrogenous material samples (ordinary paraffin of chemical structure CnH2n+2) with the same cylindrical dimensions (Ø = 8.5 cm, 0.5 cm thickness) and with the same weight of 20 g ± 0.005 for each, were used with and without the "created instrument". The neutron measurements were slowed (4.7 – 1.58 n/s) when the paraffin sample thickness was progressively increased (0 – 5 cm).  Most importantly, the "created instrument" was effectively contributed to reducing the user’s radiation exposure time from approximately 90 seconds to a few seconds no longer than 30 seconds for each measurement with considerable reduction ratio of 66.67% by making the samples of thicknesses ranging from 0.5 cm to 5 cm easier to position on the neutron beam collimator compared without using the "created instrument". It may also be utilized to evaluate the moderation on-site for different materials in neutron source shielding thickness based on the measuring procedures and data gathered. It is predicted that this study will help future improvements to use additional techniques to satisfy more protection related to the radiation field.